If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
-3*x-3 = (-1/2)*x-23 // - (-1/2)*x-23
23-3*x-((-1/2)*x)-3 = 0
(1/2)*x-3*x-3+23 = 0
20-5/2*x = 0 // - 20
-5/2*x = -20 // : -5/2
x = -20/(-5/2)
x = 8
x = 8
| -3x-2=-5/4-x | | -3x-10=-49/4 | | -3x-10=-26-x | | -3x-1/4=11/4 | | -3x-1/2=-3/7x-179/70 | | -3x-1/10=13/5 | | -3x-1=-1/3 | | -3x+9-5/7x=137/21 | | -3x+9+4x=15 | | -3x+8/9=-11/18+2x | | -3x+8/9-3x=-65/18 | | -3x+8-x=-20 | | -3x+7/10=-3/5x-9/10 | | -3x+7=9-5x | | -3x+7-3x=10 | | -3x+7+2/5x=-82/5 | | -3x+7+1/7x=83/9 | | -3x+6+x=24 | | -3x+5/7=-226/7 | | 3x-2+7=5/6 | | -3x+5/6+x=-29/66 | | -3x+5+2x=1 | | -3x+4/5=4/5 | | -3x+3/7=-102/7 | | -3x+3/4=-39/20 | | -3x+3/4=-29/4-4x | | -3x+3=-4x+17/6 | | -3x+2/9=-241/9 | | -3x+2/3=47/3 | | -3x+2/3=44/3+1/2x | | -3x+2/3+3/7x=-4/21 | | -3x+2=52/11 |